Attaining universal access: Public-private partnership and business-NGO partnership - Shyamal K. Chowdhury (University of Bonn, Center for Development Research (ZEF), 2002)
This paper evaluates two alternative mechanisms, Public-Private Partnership in Peru and Business-NGO Partnership in Bangladesh, that provide rural people with access to telecommunications. The two mechanisms that are examined here are considered as two best practices in the provision of rural telecommunications in the context of developing countries. Under two geographically distinct market segments, rural market characterized by low per-subscriber revenue and urban market characterized by high per-subscriber revenue, the traditional provision mechanisms such as state ownership, regulated monopoly and competitive market structure may not provide universal access to the people living in rural areas of developing countries. Attainment of universal access therefore may require alternative institutions. Based on three criteria of universal service provision: non-discriminatory access, uniform pricing and quality restrictions, the study finds that while the Public-Private Partnership in Peru complies with all of the three criteria, the Business-NGO partnership in Bangladesh complies with the first two criteria only. With respect to quality, users are less than satisfied with the current level of provision in Bangladesh. The success of the Business-NGO Partnership implies that the eplication of such a mechanism might require the pre-existence of an organization with local level knowledge and public good objective. In contrast to that, the Public-Private Partnership ensures the provision of universal access under a written contract, and given the public objective, can attract private providers for rural telecom provisions.
Keywords: 330; Community/Rural/Urban Development; Telekommunikation; Universaldienst; Netzregulierung; Landbevölkerung; Ländlicher Raum; Öffentlich-private Partnerschaft; Nichtregierungsorganisation; Entwicklungsländer; Peru; Bangladesch